The pattern of ocular emergencies in Lumbini Eye Institute and Research Center - Bajracharya, Kabindra; Bajracharya, Bimala; Hirachan, Anjita; Joshi, Kriti (Asian Journal of Medical Sciences, 2021)
Background: An ocular emergency is any condition in which early action is necessary to prevent severe and permanent damage to the eye. Aims and Objective: To describe the pattern of common ocular diseases presenting in emergency department. Materials and Methods: This was descriptive retrospective study conducted for the period of six months from 1st March 2019 to 31 August 2019, in emergency department of Lumbini Eye Institute and Research Center, Bhairahawa, Nepal. The data were documented from medical records in terms of age, sex, presenting visual acuity in affected eye, address and diagnosis of the disease. Results: There were total 604 patients who visited in six months period, 439 male (72.68%), 165 female (27.32%) with male to female ratio of 2.66. The patients from Lumbini Zone were 490 (81.1%), out of Lumbini Zone, Nepal were 40 (6.6%) and 74 (12.3%) were from India. There were 182 (30.1%) patients below 16 years of age. The largest number of patients were between 21-40 years comprising 41.9%. The common ocular emergencies were foreign body (13.1%), blunt trauma (11.9%), conjunctivitis (10.4%), open globe injury (10.3%) and corneal epithelial defect (9.3%). Conclusion: Most of the patients in emergency were male. The middle age patients were common followed by pediatric age group. Trauma and conjunctivitis were the most common ocular emergencies.